Prevalence and Correlates of Undernutrition in Young Children Living in Urban Slums of Mumbai, India: A Cross Sectional Study - Huey, Samantha Lee; Finkelstein, Julia Leigh; Venkatramanan, Sudha; Udipi, Shobha A.; Ghugre, Padmini; Thakker, Varsha; Thorat, Aparna; Potdar, Ramesh D.; Chopra, Harsha V.; Kurpad, Anura V.; Haas, Jere Douglas; Mehta, Saurabh (Frontiers in Public Health, 2019)
Background: Young children living in urban slums are vulnerable to malnutrition and subsequently poor health outcomes, but data on the covariates of stunting, underweight, wasting, and anemia specifically among 10-18-month-old children in India remain limited. Objective: In this analysis, we sought to describe the prevalence of and examine covariates for different markers of undernutrition, including stunting, underweight, and anemia among 10-to-18-month-old children living in urban slums, an understudied vulnerable group. Methods: Children and their mothers (n=323) were screened for anthropometry, demographics, and complete blood counts for hemoglobin concentration between March and November 2017 (Clinicaltrials.gov ID: NCT02233764). Covariates included child and mother’s age, sex, birth order, birth weight, illness episodes, hemoglobin concentration, family income, maternal height, and maternal education level. Risk ratios (RR, 95% CI) for binary outcomes (stunting, underweight, wasting and anemia) and mean differences (β, 95% CI) for continuous outcomes (anthropometric Z-scores, hemoglobin concentration) were calculated using multivariate binomial regression (SAS 9.4). Results: The prevalence of stunting was 31.2%, underweight 25.1%, wasting (9.0%), and anemia (76%) among all children. Male children had a higher prevalence of poor growth indices and lower anthropometric Z-scores than females. Male sex, low birthweight, shorter maternal height, report of ≥1 episodes of illness within the past month, older maternal age, and birth order ≥2 were also associated with poor growth and anemia in multivariate models. Covariates of undernutrition were different among females and males. Female children had a 40% (20, 60%) higher risk of anemia associated with diarrhea, and male children who were firstborn had a 20% (0, 70%) lower risk of anemia. Conclusions: These results show that poor growth and anemia among young children is prevalent in urban slums of Mumbai, and that sex of the child may play an important role in designing interventions to address undernutrition.